1990
DOI: 10.2214/ajr.155.4.2119122
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of intracranial lipoma: an MR study in 42 patients.

Abstract: Intracranial

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
330
4
21

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 274 publications
(358 citation statements)
references
References 3 publications
3
330
4
21
Order By: Relevance
“…diSCuSSion Intracranial lipomas are rare lesions, corresponding to less than 0.1% of all intracranial tumors 3,10,11 . Some authors have suggested that lipomas are congenital malformations because their lack of cellular atypia, dysplasia and other evidences of malignancy, as well as due to the fact that they are usually associated to other malformations 4,7,11 . They may originate from persistence of the meninx primitive, a precursor of pia mater and arachnoid, which develop into fat 4 .…”
Section: Casementioning
confidence: 99%
See 3 more Smart Citations
“…diSCuSSion Intracranial lipomas are rare lesions, corresponding to less than 0.1% of all intracranial tumors 3,10,11 . Some authors have suggested that lipomas are congenital malformations because their lack of cellular atypia, dysplasia and other evidences of malignancy, as well as due to the fact that they are usually associated to other malformations 4,7,11 . They may originate from persistence of the meninx primitive, a precursor of pia mater and arachnoid, which develop into fat 4 .…”
Section: Casementioning
confidence: 99%
“…Some authors have suggested that lipomas are congenital malformations because their lack of cellular atypia, dysplasia and other evidences of malignancy, as well as due to the fact that they are usually associated to other malformations 4,7,11 . They may originate from persistence of the meninx primitive, a precursor of pia mater and arachnoid, which develop into fat 4 . Most of the intracranial lipomas are pericallosal asymptomatic lesions found incidentally during neuroimaging studies 6 .…”
Section: Casementioning
confidence: 99%
See 2 more Smart Citations
“…Apesar de poderem ser encontrados no tuber cinereum, no ângulo ponto-cerebelar e na cisterna ambiens, a variedade mais conhecida e comum é aquela associada ao CC 2,3 . Foi descrita pela primeira vez em 1856 por Von Rokitanski, como um achado de autópsia 4,5 .…”
Section: Discussionunclassified